The Reporting and Help-Seeking Behaviors of Cyberstalking Victims. Issue 11 (June 2021) - Fissel, Erica R.
Crime victims are left with multiple decisions to make in an effort to cope with and recover from their experiences being criminally victimized. For example, victims must decide if they are going to report their victimization experience to law enforcement and/or if they are going to seek help from various resources, both informal and professional entities. Research on the reporting or help-seeking behaviors of cyberstalking victims is limited, but necessary to ensure that these victims are receiving the help they need. Using self-report survey data collected from a sample of 477 cyberstalking victims, this study sought to identify the characteristics of the cyberstalking victimization experience that are associated with the victim's decision to report the victimization to law enforcement, seek professional help, and seek informal help. Specifically, borrowing from Gottfredson and Gottfredson's theory of decision making, the current study explored how measures of offense seriousness and the victim–offender relationship are associated with cyberstalking victims' reporting and help-seeking behaviors. The findings revealed that cyberstalking victims who experienced more serious offenses had increased odds of engaging in reporting and both types of help-seeking behaviors. Furthermore, victims who were cyberstalked by their current intimate partner had greater odds of engaging in reporting and professional help-seeking behaviors. As this study is just one of many that are needed to gain a better understanding of the reporting and help-seeking behaviors of cyberstalking victims, directions for future research are provided.